2003
DOI: 10.1046/j.1523-1747.2003.12407.x
|View full text |Cite
|
Sign up to set email alerts
|

Exacerbated and Prolonged Allergic and Non-Allergic Inflammatory Cutaneous Reaction in Mice with Targeted Interleukin-18 Expression in the Skin

Abstract: Interleukin 18 induces both T helper 1 and T helper 2 cytokines, proinflammatory cytokines, chemokines, and IgE and IgG1 production. A role of interleukin 18 in inflammatory cutaneous reactions is still unclear, however. Here we generated keratin 5/interleukin 18 transgenic mice overexpressing mature murine interleukin 18 in the skin using a human keratin 5 promoter. In the contact hypersensitivity model, trinitrochlorobenzene elicited a stronger ear swelling in keratin 5/interleukin 18 transgenic mice compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 33 publications
0
31
0
1
Order By: Relevance
“…The role of IL-18 has not been examined in models of psoriasis. However, it has been shown that transgenic mice overexpressing IL-18 develop a severe and persisting skin reaction in response to topical irritants (146).…”
Section: Psoriasismentioning
confidence: 99%
“…The role of IL-18 has not been examined in models of psoriasis. However, it has been shown that transgenic mice overexpressing IL-18 develop a severe and persisting skin reaction in response to topical irritants (146).…”
Section: Psoriasismentioning
confidence: 99%
“…In addition, associations between levels of some Th1 cytokines, such as IL-2 (4) and , and prognosis in several cancers have been reported, suggesting that serum levels of specific cytokines can be used as prognostic makers in patients with some cancers. (6,(9)(10)(11)(12)(13)(14). (21).…”
Section: Non-small Cell Lung Cancer (Nsclc) Is the Most Common Type Omentioning
confidence: 99%
“…Additionally, it has been reported that overexpression of IL-18 in the skin aggravates allergic and non-allergic cutaneous inflammation (Kawase et al 2003). These findings suggest that excessive IL-18 in the gingival tissues could be a key stimulator of periodontal disease.…”
Section: Introductionmentioning
confidence: 93%
“…IL-18Tg mice with a C57BL/6N background (8-10 weeks old) were kindly provided by T. Hoshino (Kurume University, Kurume, Japan). In these mice, keratinocytes express mouse IL-18 fused to the signal peptide of the mouse immunoglobulin κ-chain, under the control of the human keratinocyte K5 promoter (Kawase et al 2003). Age-matched wild-type (WT) C57BL/6N mice were purchased from Charles River Japan (Yokohama, Japan).…”
Section: Micementioning
confidence: 99%